A novel NiCoMnO4 anode material: Construction of nanosheet architecture and superior electrochemical performances. (15th March 2018) - Liu, Mengjiao; Wang, Li; Mu, Yanlin; Ma, Jianmin; Zhao, Yan; Wang, Yi; Lai, Xin; Bi, Jian; Gao, Daojiang
Abstract: Novel NiCoMnO4 nanosheets have been designed and fabricated via a facile hydrothermal derived process. The microstructure results reveal that the as-prepared material has a typical spinel structure and possesses a nanosheet morphology. Due to the unique chemical composition and nanostructure, the NiCoMnO4 nanosheets exhibit a very high reversible capacity of 1329.3 mAh g − 1 at 200 mA g − 1 after 100 cycles and show excellent rate performance of 501.6 mAh g − 1 even at 5000 mA g − 1 when used as anode material for lithium-ion batteries (LIBs). Graphical abstract: Image 2